2017
DOI: 10.18533/ijbsr.v7i3.1040
|View full text |Cite
|
Sign up to set email alerts
|

Linkages among E-Service Quality, Satisfaction, and Usage of E-Services within Higher Educational Environments

Abstract: To date, literature on e-service quality (E-SQ) has mainly been on conceptualisation and measurement issues within the e-retail environments. Empirical research on E-SQ and its consequences in 'pure' service context has not been forthcoming. In expanding knowledge in light of this, this study examined a modified E-SQ scale within a university's e-services setting. In addition, the linkages existing among E-SQ (in this 'pure' service environment) and satisfaction and e-service usage frequency was estimated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
5
12
0
2
Order By: Relevance
“…Online services for students include enrollment, course delivery, payment, course support, and libraries (Sutarso & Suharmadi, 2011). The campus does not ignore the growing trend in student demand as customers to provide services electronically (Ataburo, Muntaka, & Quansah, 2017). Universities should be at the forefront of online activities (Kim-Soon, Rahman, & Ahmed, 2014).…”
Section: Figure 2 Path Diagrammentioning
confidence: 99%
“…Online services for students include enrollment, course delivery, payment, course support, and libraries (Sutarso & Suharmadi, 2011). The campus does not ignore the growing trend in student demand as customers to provide services electronically (Ataburo, Muntaka, & Quansah, 2017). Universities should be at the forefront of online activities (Kim-Soon, Rahman, & Ahmed, 2014).…”
Section: Figure 2 Path Diagrammentioning
confidence: 99%
“…• service interaction quality (sub-dimensions trust and empathy): transaction/information security, product delivery, personalization, and communication with website. Ataburo, Muntaka, and Quansah (2017) stated that e-services should be designed to support the interactive flow of information between the customer and service provider. They indicated that the nature of e-service is to provide the customer with great experience with respect to the interactive flow of information.…”
Section: Perceived E-service Qualitymentioning
confidence: 99%
“…Fenomena perubahan bisnis saat ini terjadi juga pada bisnis online. Masyarakat tidak lagi mengandalkan berbelanja offline yang membutuhkan waktu ekstra dan beralih berbelanja kebutuhan melalui sosial media (Ataburo et al, 2017). Berbelanja melalui sosial media secara online memberikan kemudahan dapat dilakukan di mana saja, kapan saja dengan variasi harga yang relatif bersaing (Piarna, 2014).…”
Section: Pendahuluanunclassified
“…Sebagian menjadi penyebab dan sebagian lain menjadi akibat. Studi ini menguji hipotesis yang menjelaskan variabel kualitas layanan online (X) sebagai variabel eksogen, variabel customer perceived value (M) sebagai mediasi dan keputusan pembelian (Y) sebagai variabel endogen Populasi adalah seluruh subjek atau objek yang diteliti yang memiliki kualitas serta karakteristik yang telah ditetapkan (Ataburo et al, 2017) Populasi dalam penelitian ini adalah semua orang yang pernah melakukan pembelian pada produk tas merk PALOMINO pada Zalora di Kota Denpasar.…”
Section: Metode Penelitianunclassified